Coffee with Marilyn - McDonough, Yona Zeldis (London Ducan Baird Publishers, 2007)
Presents a fictionalized interview with Marilyn Monroe, where she discusses topics such as fame, past loves, and her thoughts the night she died.
Include Index
Keywords: United States -- Motion Picture Actors and Actresses